EaseDB: a cache-oblivious in-memory query processor - He, Bingsheng; Li, Yinan; Luo, Qiong; Yang, Dongqing (Proceedings of the ACM SIGMOD International Conference on Management of Data, Beijing, China, June 12-14, 2007, 2007)
We propose to demonstrate EaseDB, the first cache-oblivious queryprocessor for in-memory relational query processing. The cache-oblivious notion from the theory community refers to the property that no parameters in an algorithm or a data structure need to be tuned for a specific memory hierarchy for optimality. As a result, EaseDB automatically optimizes the cache performance as well as the overall performance of query processing on any memory hierarchy. We have developed a visualization interface to show the detailed performance of EaseDB in comparison with its cache-conscious counterpart, with both the parameters in the cache-conscious algorithms and the hardware platforms varied.